Direito e desenvolvimento no Brasil: um estudo sobre o microempreendedor individual - Oliveira, George Felício Gomes de (2017)
The essence of development is to improve the quality of life of disadvantaged people. The action against poverty and the respect for human dignity are strategies able to alter reality. For this, it is recommended that the notion of development is uncoupled the narrow space of the economy and expand your horizon in attention to human freedom. If, on the one hand, free is one that can move without abusive obstacles to the exercise of their rights, on the other side aim to face the freedom according to which the subject the necessary tools are available to full performance capabilities. It is argued that, in Brazil, such means have always been out of reach of most people. So much so that the country, despite the greatness of its economy, never joined the ranks of the so-called developed countries. Is investigated in this study, an initiative that aims to influence change in this scenario: the Individual Microentrepreneur Program. Established from the Complementary Law no. 128/2008, this legal institute allows certain categories of informal workers to legalize as small business owners, becoming thus welcomed by a state public policy. Examines, in this work, the foundations of this structure, seeking primarily relate it to the law and development field. In addition, we intend to demonstrate that there are reasons to believe in the correctness of this contract for the development of a free corporate citizenship historically exclusionary bureaucracy. Through interdisciplinary research, its verified the impact of this measure in the Brazilian legal system, in the economic system and in the daily lives of many men and women under his mantle welcomed.